Therapeutic embolization of the bronchial and intercostal arteries in hemoptysis - Tiscornia, Eduardo; Sálice, Mario; Pereyra, Daniel; Muras, Olga; González, Alvaro; Frejeiro, Roberto; Pratt, Gilberto; Grolero, Maria; Trenchi, Atilio; Piñeyro, Luis; et al. (Cirugía del Uruguay, 1979)
This review of 11 cases of therapeutic embolization of bronchial and intercostal arteries in patients suffering from hemoptysis comprises an analysis of method, comprications and results. This method is important in stopping serious hemoptysis in cases where surgery is contraindicated.